Potential osteogenic activity of ethanolic extract and oxoflavidin isolated from Pholidota articulata Lindley. (21st July 2015) - Sharma, Chetan; Dixit, Manisha; Singh, Rohit; Agrawal, Manali; Mansoori, Mohd Nizam; Kureel, Jyoti; Singh, Divya; Narender, Tadigoppula; Arya, Kamal Ram
Abstract: Ethnopharmacological relevance: Pholidota articulata Lindley (PA) locally known as Hadjojen (bone jointer) belongs to family Orchidaceae is used for healing fractures in folklore tradition of Kumaon region of Uttarakhand, Himalaya, India. Bone is a dynamic organ and is constantly being remodeled in order to facilitate growth and repair. This process requires the involvement of bone forming osteoblast and bone resorbing osteoclast cells, which function in generating and mineralizing bone, giving strength and rigidity to the skeletal system. Present study was aimed to determine the therapeutic potential of ethanolic extract of PA and its isolated compound oxoflavidin, by characterizing their fracture healing properties. Materials and methods: Ovariectomized (Ovx) estrogen deficient adult female Balb/c mice were used for in vivo evaluation of osteogenic or bone healing potential of ethanolic extract of PA. Further, its isolated compounds were tested for their osteogenic efficacy using alkaline phosphatase assay and mineralization assay in vitro in mice calvarial osteoblasts. Results: The ethanolic extract of PA exhibited significant restoration of trabecular micro-architecture in both femoral and tibial bones. Additionally, treatment with PA extract led to better bone quality and devoid of any uterine estrogenicity in ovariectomized estrogen deficient mice. One of the isolated compound, oxoflavidin enhanced ALP activity (a marker of osteoblast differentiation), mineral nodule formation and mRNA levels of osteogenic markers like BMP-2, Type 1 Collagen, RUNX-2 and osteocalcin. Conclusion: These results warrant that ethanolic extract of PA and it's pure compound oxoflavidin have fracture healing properties. The extract and oxoflavidin exhibit a strong threapeutical potential for the treatment and management of postmenopausal osteoporosis.